Forest protected areas: time is running out - Sayer, Jeffrey A. (2000)
Extensive areas of forest in the tropics have been legally classified as protected areas: however, in many cases it has been difficult to achieve their conservation. This paper argues that the priority for forest conservation should not be maximising the area totally protected but rather to focus on improved management effectiveness. The keys to improved management will be greater clarity in defining objectives and a greater commitment to finding locally appropriate conservation approaches. This in return will suggest that a portfolio of different approaches to forest protection will have a higher chance of success than maximising the area allocated to arbitrary international frameworks. Practical realities will dictate that the portfolio will include a range of options from elite sites given exemplary protection to well-managed multiple-use areas where protection and use are balanced. It is argued that in tropical countries with large populations of poor people multiple-use areas will have an especially valuable role to play. An ‘ecosystem approach’ to the management of these areas is proposed and practical ways to develop this approach are suggested. An ecosystem approach will require that conservation agencies move away from ‘command and control’ management and adopt output-based systems on effective collaboration between all stakeholders